STRATEGI KEUNGGULAN KEPRIBADIAN EFEKTIF KEPALA SEKOLAH DAN PROFESIONALISME GURU SEBAGAI FONDASI PENDIDIKAN BERKUALITAS - Hero Gefthi Firnando (Pascasarjana Unviersitas Majalengka, 2023)
Personality is a characteristic inherent in individuals and can be influenced by the environment, especially in the context of leadership where personality has various elements that become the power to direct positive change. The aim of this research is to examine the personality development strategies of school principals and teachers in influencing the school community to improve school quality and learning. The research method used is library research. Thus, we can conclude that school principals and teachers need to have personality competence to be able to move students and society towards sustainable change. Through this personality competency, the principal as a leader can be an example for teachers, while teachers, as the front guard, can be role models for students. In this way, the quality of education can be improved.